Spectrum of Neonatal Pneumothorax at a Tertiary Care Hospital of Bangladesh : A Retrospective Observational Study. - Mannan, Md Abdul; Dey, Sanjoy Kumar; Jahan, Nasim; Iqbal, Shahed; Karim, SM Rezaul; Ferdous, Navila (Bangladesh Critical Care Journal, 2019)
Introduction: Pneumothorax occurs more frequently in the neonatal period than in any other period of life & is associated with increased mortality and morbidity. Several risk factors for pneumothorax, including respiratory pathology, invasive and non-invasive respiratory support & predictors of mortality have been described. Objective: To evaluate the prevalence of pneumothorax, to identify underlying causes & to describe the clinical characteristics, management and outcome of neonates with pneumothorax, as well as to identify predictors of mortality in these neonates. Methods: A retrospective chart review of neonatal records included all neonates hospitalized in the NICU of 'Ad-din Women’s Medical College' Dhaka, between January 2016 & December 2017 with the diagnosis of pneumothorax. The collected data included: demographics & perinatal data, characteristics of pneumothorax, classification, treatment & clinical outcomes. All statistical analyses were performed using the Statistical Package for Social Sciences (SPSS) version 16. Results: Our study included 83 neonates, of whom 48 were male (57.83%) & 60 (72.29%) born by lower uterine caesarean section (LUCS). Median gestational age(GA) was 36 (32-41) weeks & the median birth weight(BW) was 2,558 (1500-3800) grams. The prevalence of neonatal Pneumothorax in our centre was 2.60% & that of Spontaneous Pneumothorax was 1.53%. The analysis of perinatal data showed statistically significant differences in APGAR score at 5th minute (p = <0.00001) & in resuscitation at birth (p < 0.00001). Pneumothorax was significantly associated with RDS, pneumonia, Meconium aspiration syndrome (MAS) & Perinatal asphyxia (PNA), (p=0.235893) and all (n=6) death were observed in neonates who had coexisting diseases, (p=0.00226). Forty nine (59.04%) was SP (p = 0.002) & mainly observed in the right lung (77.11 %( (p=0.00011). To treat the pneumothoraces, 64 (77.11%) neonates only received oxygen therapy, 16 (19.28%) neonate needed MV along with chest tube (CT) drain, 02(2.41%) thoracentesis with needle aspiration, and 01 (1.20%) needle aspiration & chest tube (CT) drain (p <0.00001). Clinical data suggest that complications such as sepsis, severe hypotension, Necrotizing enterocolitis (NEC), DIC, Intraventricular haemorrhage (IVH) can negatively affect immediate outcomes (p=0.00025). The mortality rate was 7.23%. All the mortalities observed in neonates who got respiratory support with mechanical ventilation (MV) along with CT insertion (p=<0.00001). Hypotension, sepsis, DIC, IVH, MV and thoracentesis followed by a CT insertion were found to be predictors of mortality in neonates with pneumothorax. Conclusion: NP may develop during the neonatal period, especially in the presence of underlying clinical conditions, and neonates with pneumothorax managed with CT drain and respiratory support (MV), despite treatment have a high mortality rate. Bangladesh Crit Care J March 2019; 7(1): 12-19